Propuesta de un medio institucional de prensa para la Fundación Filarmónica Casa de la Música y aplicación de nuevas tecnologías de la información y la comunicación (Tics) en su página web - Troya Porras, María Belén (2010)
The Philharmonic Foundation “Casa de la Música” is a Non profitable Institution which main activity is the diffusion of culture, specifically related to music. It periodically presents great interpreters, either national or foreigners. It also has a great variety of costs, from 100 dollars to free events. However, its positioning in the society is perceived as directed to high status; consequently, during the presentations, there is a significant absenteeism due to the lack of diffusion and marketing. The first two chapters of this investigation pretend to expose the characteristics of each one of the existing Means of Communication, with their advantages and disadvantages, considering as its principal basis the service to Journalism, relating them to the Institutional Journalism and looking for the one that best suits the modern tendencies of this activity. We must consider the parameters to follow in order to find the balance that allows an Institutional means of communication to accomplish the journalistic ethics, and not become a mere means of promotion. The third chapter exhibits the reality of the Foundation, its needs and possibilities, as well as its work and legacy. The present investigation pretends to determine which is the people is opinion who attend the events, in relation to the information that the entity offers, with the idea of elaborating a proposal from the ethical and professional view, which might help to accomplish its main mission: “diffuse, interest, educate and appreciate the music, keeping high standards of quality”. For this purpose, three investigation tools have been used: corporative workshop, interviews with experts and surveys. The results obtained show a considerable level of permanent lack of information, which leads to the necessity of creating printed institutional means of communication, and improve the interaction and contents in the current Web Page of the Foundation.